2014
DOI: 10.1016/j.molbiopara.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The single epsin homolog in Giardia lamblia localizes to the ventral disk of trophozoites and is not associated with clathrin membrane coats

Abstract: Epsins serve as recruitment platforms for clathrin membrane coat protein components and induce membrane curvature via their N-terminal homology (ENTH) domain. Unexpectedly, the single ENTH domain protein, a putative epsinR homolog (Glepsin), in the diverged protozoan parasite Giardia lamblia, localizes exclusively to the specialized attachment organelle, the ventral disk (VD). Glepsin binds both to phosphatidylinositol (3,4,5)-trisphosphate phospholipids and the VD cytoskeleton, but lacks canonical domains for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Only when GlENTHp was At the time we were performing this analysis, another group published new results about GlENTHp (13). Surprisingly, they found that GlENTHp localized in the giardial ventral disk, a microtubule structure and the primary organelle of attachment to the cell host (13). One explanation of this differential behavior of the protein might be just a technical problem since the cytosolic and the membrane distribution of GlENTHp was demonstrated by biochemical and cellular analysis in our work.…”
Section: The Multiple Function Of Glenthpmentioning
confidence: 70%
See 1 more Smart Citation
“…Only when GlENTHp was At the time we were performing this analysis, another group published new results about GlENTHp (13). Surprisingly, they found that GlENTHp localized in the giardial ventral disk, a microtubule structure and the primary organelle of attachment to the cell host (13). One explanation of this differential behavior of the protein might be just a technical problem since the cytosolic and the membrane distribution of GlENTHp was demonstrated by biochemical and cellular analysis in our work.…”
Section: The Multiple Function Of Glenthpmentioning
confidence: 70%
“…Thus, we decided to test whether the dominant negative effect of GlENTHp overexpression was related to a change in the localization of Ent3/5p by overexpressing GlENTHp, gENTH and the mutant that is unable to bind PIs. Only when GlENTHp was At the time we were performing this analysis, another group published new results about GlENTHp (13). Surprisingly, they found that GlENTHp localized in the giardial ventral disk, a microtubule structure and the primary organelle of attachment to the cell host (13).…”
Section: The Multiple Function Of Glenthpmentioning
confidence: 99%
“…Their extended interactomes and their involvement in fluid-phase uptake have yet to be investigated but current data point towards a complex network of PIP binders of varying binding preference and affinity, all working in the same subcellular environment, yet, in some cases ( Gl FERM, Gl BAR1 and 2, Gl PROP1 and 2, Gl16801), not directly linked to clathrin assemblies. The only known exception is Gl epsin whose localization remains controversial due to conflicting reports [21, 69]. We systematically did not detect Gl epsin in any of the interactomes for clathrin-associated PIP binders, in line with its localization at the ventral disk [21].…”
Section: Discussionmentioning
confidence: 87%
“…The only known exception is Gl epsin whose localization remains controversial due to conflicting reports [21, 69]. We systematically did not detect Gl epsin in any of the interactomes for clathrin-associated PIP binders, in line with its localization at the ventral disk [21]. Altogether, the variety of PIP residues and PIP-binding modules in the G. lamblia cortical area containing endocytic PVs underscores their necessity for correct functioning of membrane traffic even in a protist so clearly marked by reduction in endomembrane complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Given that several types of PIP-binding modules have been identified in eukaryotes, we determined how many endocytosis-associated module types were actually represented in the Giardia genome, in addition to the known G. lamblia epsin, FYVE and PXD variants [19][20][21][22][23]. For this reason, we selected a total of 14 protein types from various organisms known to harbour PIP-binding domains, some of them involved in endocytosis.…”
Section: The G Lamblia Genome Encodes At Least Seven Distinct Pip-bimentioning
confidence: 99%